Effects of nanoclay on the properties of low temperature cured polyimide system - Kim, Kwangin; Yoo, Taewon; Nam, Ki-Ho; Han, Patrick; Jang, Wonbong; Han, Haksoo (Macromolecular research, 2014)
Polyimide is a major polymer material in the electronics industry, and we conducted a study to cure polyimide at low temperatures in order to improve its thermal and mechanical properties. In this study, polyimide/clay nanocomposites were prepared by the reaction of 4,4’-(hexafluoro isopropylidene) diphthalic anhydride (6FDA) and 4,4’-oxydianiline (ODA) with the addition of 1,4-dizabicyclo[2.2.2]octane (DABCO) as a low-temperature catalyst and nanoclay (Cloisite 20A). The synthesis of polyimide at low temperatures and the dispersion of a nanoclay in the polymer matrix was confirmed by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), respectively. Thermal stabilities of the nanocomposites were confirmed by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The mechanical properties were measured by an universal testing machine. We demonstrated that when polyimide was cured at low temperatures and short curing times, it was possible to improve the thermal and mechanical properties via the addition of a catalyst and inorganic material. Polyimide with DABCO and 0.25 wt% nanoclay showed a 5 °C higher degradation temperature, 560.88 °C; a 6 °C higher glass transition temperature, 293.62 °C; and a 20 MPa greater tensile strength, 136.94 MPa. Therefore, the polyimide curing process was demonstrated to be successful at low temperatures.